Timeliness of Annual Reports of Listed Companies in Malaysia - Fong, Yuh Leng (2009)
Whilst timeliness has long been recognised as one of the important characteristics to determine the relevance of accounting information, the timeliness of annual reporting has not been examined in any substantial way in Malaysia. This study not only examines the timeliness of annual reports published by companies listed on the stock exchange of Malaysia, that is, the Bursa Malaysia Securities Berhad (Bursa Malaysia), it also aims to determine whether there is any correlation between timeliness and a company‟s attributes in terms of corporate size, profitability, growth, capital structure, composition of board of directors and quality of internal controls. This study involves an analysis of the timeliness of annual reports of a sample of 250 companies listed on Bursa Malaysia, spread across all industry sectors from the main board, second board and mesdaq with the companies‟ financial year end cut off date as at 31 October 2008 and publication cut off date as at 30 April 2009 (Bursa Malaysia announcement date). The results of the analysis and the implications are discussed. Several hypotheses were tested concerning the relationship between timeliness and the six selected corporate attributes. This study reveals that all, except one company or 0.4%, reported within the statutory deadline of six months from the respective company‟s financial year end. Whilst, 33.6% of the sample companies took most of the time given to announce their annual reports, only one company or 0.4% announced their annual results as early as 35 days after their financial year end. The majority or 59.6% of the sample companies took between three to five months to submit their annual reports. The study also provides evidence that there is significant correlation between timeliness and each of the six corporate attributes, and the correlation is in the hypothesised direction. Plausible explanations for these findings are provided. The findings may provide some implications for future regulations and research regarding the timeliness of annual reporting in Malaysia.